Komitmen Organisasi pada Dosen Generasi Milenial - Reza Lidia Sari (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2018)
In Human Resource Management, workers from the millennial generation, including those working as lecturers in Indonesia, are often studied with regard to their low level of organizational commitment. Millennial lecturers are often faced with various challenges that can trigger them to decide to quit their jobs and leave the college. This research aimed to discover the factors influencing millennial lecturers’ organizational commitment. The instruments used were the Organizational Commitment Scale, Job Satisfaction Survey, and Professional Commitment Scale. The respondents were 123 lecturers from 10 universities in Padang, Jakarta, and Bali, who were selected using purposive sampling technique. The analysis method used was a multiple regression analysis. The research findings showed that job satisfaction and professional commitment, to be exact, their satisfaction with supervisors, professional commitment continuance and normative professional commitment had a significant impact on these lecturers’ organizational commitment. The result of this study delivers important implications to universities in managing their millennial lecturers so that they can improve their organizational commitment.